Protective factors enhancing resilience in children of parents with a mental illness: a systematic review - Van Schoors, Marieke; Van Lierde, Elke; Steeman, Kim; Verhofstadt, Lesley L.; Lemmens, Gilbert M. D. (Frontiers in Psychology, 2023)
Objectives: A systematic review was conducted to (1) investigate protective factors enhancing resilience in children of parents with a mental illness (COPMI), and (2) examine theoretical and methodological issues in the existing literature. Method: Following guidelines for systematic reviews, searches were performed using Web of Science, Pubmed and Embase. After screening 5,073 articles 37 fulfilled inclusion criteria and were extracted for review. Results of the present review indicate that there are several ways to help build resilience in COPMI. More specifically, five protective factors emerged from the reviewed literature: Information, Support, Family functioning and Connectedness, Child coping and Parenting. Discussion: Research on protective factors in children confronted with parental mental illness is still scarce and for some factors no clear conclusions can be drawn based on the available evidence. To further our understanding of the building blocks and underlying mechanisms of resilience in COPMI, additional rigorously designed studies are needed.